Validity and Reliability of AISIRE to Measure the Reaction Speed of Upper Elementary School Students - Zainal, Hary; Lestari, Resti Kamiarti; Ginanjar, Agi (Universitas Pendidikan Indonesia, 2021)
Simple Innovation Tools for Reaction Indications (AISIRE) is an instrument to measure reaction speed of Elementary School students grade 4, 5, 6 or upper Elementary schools. A good instrument must have validity and reliability that meet statistical criteria. The purpose of this study was to determine the validity and reliability of AISIRE, specifically to find out if AISIRE could be used as an instrument in measuring the reaction speed of upper Elementary School students. The research method used descriptive research methods with a quantitative approach. The participants participated in this study were 78 students (39 males and 39 females) at the upper level of Elementary School selected using incidental sampling technique. The data collection technique employed a test with AISIRE as the research instrument. The data analysis technique used correlation test, Norm Referenced Evaluation, and Criterion Referenced Evaluation. This study concludes that AISIRE can be used as an instrument in measuring the reaction speed of upper Elementary School students. ASIRE can meet the validity and reliability according to statistical criteria. Further research regarding distance in AISIRE and instrument development utilizing the development of existing technology is needed.